Immersive worlds as educational environments - Banek Zorica, Mihaela (Array, 2009)
Immersive worlds are rapidly entering the educational environments and thereby putting new requirements and tasks in front of both teachers and students. Together with the possibilities and full potentials of Web 2.0 environment (which in some cases are attempting to offer 3D spaces to their users) they are expanding current higher education e-learning systems. Authors give an overview of the current virtual world representation and its research in educational and library environment. Based on first phase of implementation of one of these virtual worlds (Second life) at the Department of Information Sciences, Faculty of Humanities and Social Sciences, University of Zagreb authors show both pros and cons of its implementation in higher education learning environment.